Hospitality And Tourism Industry Performance in Indonesia Based on Benjamin Graham’s Perspective - Yulita, Ima Kristina; Rahayu, Caecilia Wahyu Estining (JURNAL ILMU MANAJEMEN DAN BISNIS, 2019)
Abstract. This research aims at determining the performance of hospitality and tourism industry in Indonesia based on the analysis of financial ratios using the Benjamin Graham’s perspective. The total number of samples is 9 companies listed in Indonesia Stock Exchange in 2012-2016. The analysis of financial ratios includes Earning Per-Share (EPS), Price to Earnings Ratio (PER), Price to Book Value (PBV), Return on Equity (ROE), Current Ratio (CR) and Debt to Equity Ratio (DER). First, this research examined the effects of those six financial ratios on stock prices either partially or simultaneously. Afterwards, only financial ratios that had a significant effect on stock prices are analyzed using Benjamin Graham. Hypothesis testing was conducted using Multiple Linear Regression analysis. The results point out that: (1) EPS, PER, PBV, ROE, CR and DER simultaneously affect the stock prices; (2) EPS, PER, PBV and DER partially affect the stock prices; (3) Seven companies that meet 2 of 4 determined criteria are ARTA, BAYU, JIHD, JSPT, KPIG, PDES and SHID. The results of this research are expected to provide recommendations for investors in selecting companies’ shares with good performance based on 4 financial ratios.Keywords. Hospitality and tourism industry, financial ratio, financial performance, stock prices, Benjamin Graham. Abstrak. Penelitian ini bertujuan untuk mengetahui kinerja industri hotel dan pariwisata di Indonesia berdasarkan analisis rasio keuangan menggunakan perspektif Benjamin Graham. Jumlah sampel adalah 9 perusahaan yang terdaftar di Bursa Efek Indonesia pada tahun 2012-2016. Analisis rasio keuangan termasuk Earning Per-Share (EPS), Price to Earnings Ratio (PER), Price to Book Value (PBV), Return on Equity (ROE), Current Ratio (CR) dan Debt to Equity Ratio (DER) . Pertama, penelitian ini menguji pengaruh dari enam rasio keuangan terhadap harga saham baik secara parsial maupun secara simultan. Setelah itu, hanya rasio keuangan yang memiliki pengaruh signifikan terhadap harga saham yang dianalisis menggunakan Benjamin Graham. Pengujian hipotesis dilakukan menggunakan analisis Regresi Linier Berganda. Hasil menunjukkan bahwa: (1) EPS, PER, PBV, ROE, CR dan DER secara simultan mempengaruhi harga saham; (2) EPS, PER, PBV dan DER secara parsial mempengaruhi harga saham; (3) Tujuh perusahaan yang memenuhi 2 dari 4 kriteria yang ditentukan adalah ARTA, BAYU, JIHD, JSPT, KPIG, PDES dan SHID. Hasil penelitian ini diharapkan dapat memberikan rekomendasi bagi investor dalam memilih saham perusahaan dengan kinerja yang baik berdasarkan 4 rasio keuangan.Kata kunci : industri hotel dan pariwisata, rasio keuangan, kinerja keuangan, harga saham, Benjamin Graham